ИНТЕЛЛЕКТ – КРЕАТИВЛИК ҚӘБИЛЕТТИҢ РАЎАЖЛАНЫЎЫНЫҢ ӘҲМИЙЕТЛИ ТИЙКАРЫ СЫПАТЫНДА - Тлеумбетова, Қ.Д. (FAN va JAMIYAT, 2020)
The article is about the peculiarities of intellectual development of pre-school children, the results of children’s development of mental, intellectual and logical thinking skills in pre-school classes.